Analysis of programme outcomes achievement for electrical engineering programmes in UNITEN - Amirulddin U.A.U.; Osman M.; Hamid F.A. (2023)
In Outcome-Based Education approach, Programme Outcomes (PO) is a series of technical and non-technical skills that a graduate from an institution should acquire prior to graduation. The qualities in the PO are usually closely related to the training that the student has gone through. The attainment of PO must be tracked at every semester and corrective actions must be implemented if the attainment does not meet the performance criterion that has been set. This implies a need for a continuous quality improvement (CQI) process for PO attainment. This paper presents the analysis of PO achievement based on student's achievement in formal assessments for core subjects in the Bachelor of Electrical Power Engineering (BEPE) and Bachelor of Electrical and Electronics Engineering (BEEE) programmes in UNITEN for four semesters from Semester 1, 2007/2008 to Semester 2, 2008/2009. In general, all POs are attained by both programmes. However, it was observed that with the current performance criteria a decline in soft skills PO achievement was observed. Hence, a new PO attainment strategy was devised and a new performance criterion has been set. This paper aims to highlight the CQI processes in place to analyze the BEPE and BEEE Programme Outcomes attainment. 2009 IEEE.